Today's Technician: Automotive Suspension and Steering Systems - Knowles, Don (Thomson Delmar Learning, 2006)
Don Knowles is the owner and manager of Knowles Automotive Training in Moose Jaw, Saskatchewan, Canada. He is a member of several organizations, such as, Society of Automotive Engineers (SAE), the Service Technicians Society (STS), North American Council of Automotive Teachers (NACAT) and Council of Advanced Automotive Trainers (CAAT). He is an ASE Master Technician Automotive and he is an ASE advanced Engine Performance LI certified.